Analysis of water conveying aluminum oxide/silver nanoparticles due to mixed convection through four square cavity's variable hot (cold) walled - Roubi Abdelhak; Fares Redouane; Wasim Jamshed; Mohamed R. Eid; Kamel Guedri; M. Israr Ur Rehman; Sayed M. El Din (Ain Shams Engineering Journal, 2023)
The present work focuses on the measurement of the general entropy and the heat exchanges that occur inside a square-shaped cavity by changing the cold and hot wall in four cases filled with a hybrid nano-liquid (Al2O3-Ag/water) with a cylinder installed inside it. After validating the model, the parametric study has been conducted based on Rayleigh number (Ra), Hartman number (Ha), Darcy number (Da), Solid volume fraction (φ) and Porosity (ε) aspects. An effective finite element method was employed to solve the problem of flow in a dimensionless form of governing equations towards flow and thermal behaviors of nanofluid which is laminar and incompressible. Using the COMSOL Multiphysics® software computer suite, the equations for energy, motion, and continuity were resolved. Nusselt number calculations are presented to quantify heat transport via mixed convection. In the case studies, the entropy generation improves regardless of where the heated wall is located, except for the third case, where it is higher than the others. The findings are demonstrated with a higher Rayleigh number Ra, average Nusselt number, and entropy production. The heat transfer rate (HTR) can be effectively adjusted by making use of the magnetic field. The process of producing entropy in the third cavity, where the hot wall mediates the right wall, is the crucial observation made through this effort.